Paying not to sell - Emanuele Bacchiega; Olivier Bonroy; Rania Mabrouk (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2013)
In this paper we show that, in the presence of buyer and seller power, a monopolist can enter into a costly contractual relationship with a low-quality supplier with the sole intention of improving its bargaining position relative to a high-quality supplier, without ever selling the good produced by that firm.
Keywords: L12; L13; L14; 330